Educational Strategy for Regeneration of Child Dancers in Satrio Bokor Tumpang Group - Suprihatin, Endang Wara; Sumarwahyudi, Sumarwahyudi; Hidajat, Robby; Zandra, Rully Aprilia; Yatim, Heriyati; Rahman, Amalia Arifah (Gondang: Jurnal Seni dan Budaya, 2024)
Regeneration of traditional arts is an important thing that really needs to be done because it is a strategic step in maintaining the sustainability of local culture. Jaranan thrives in the Tumpang area, but only the Satri Bokor group has a group of children aged 6 to 15 years. This research was specifically conducted to analyse the regeneration strategy for child Jaranan dancers carried out in the Satrio Bokor Tumpang Group, Malang Regency. The research method uses a qualitative descriptive approach, where data is obtained through observation, interviews and documentation. The research results show that the regeneration strategy is carried out through routine training every afternoon after school, a family approach, and involvement in Jaranan performances and YouTube social media promotions. The main challenges faced are competition with other emerging arts, namely Bantengan, limited funds, and children's time commitment. However, this regeneration has had a positive impact on preserving culture and forming the character of the younger generation. In conclusion, the regeneration strategy implemented by the Satrio Bokor Group is effective in involving children in loving and preserving Jaranan art, although further support from various parties is needed.